Circulating Serum Amyloid A, hs-CRP and Vitamin D Levels in Postmenopausal Osteoporosis: - Safari, Anahid; Borhani-Haghighi, Afshin; Dianatpour, Mehdi; Heydari, Seyed Taghi; Foroughinia, Farzaneh; Ranjbar Omrani, Gholamhossein (Galen Medical Journal, 2019)
Background: Both vitamin D and inflammation were investigated as important players in the pathogenesis of postmenopausal osteoporosis. This study compared vitamin D, inflammatory the biomarkers serum levels and their association with bone mineral density (BMD) in case and control groups to evaluate the possible immune-regulatory effect of vitamin D in this population. Materials and Methods: Participants in post-menopausal age, were categorized to 44 osteoporotic vs. 44 healthy aged-matched women according to WHO criteria. Total BMD, T- scores, Z-scores as well as fracture risk were measured in both groups, using Hologic system Dual-energy X-ray absorptiometry (DEXA). Serum 25-OH vitamin D, high sensitive CRP (hs-CRP) and serum amyloid A (SAA) were compared between groups. The association between serum biomarkers level and BMD were also investigated. The same evaluations were performed for vitamin D deficient (<20 ng/mL) and non-deficient (≥20 ng/mL) subgroups. Results: Vitamin D deficiency was higher in the osteoporotic group (32.6%) in comparison with the control group (25.6%), but the differences were not significant (P=0.47). There were no significant differences in serum levels of hs-CRP and SAA (P=0.83 and P=0.39) as well. No significant association between serum inflammatory biomarkers, vitamin D, and BMD were detected (P≥0.05). The results were the same for vitamin D deficient and non-deficient subgroups (P≥0.05). Conclusion: In the current study, the beneficial effects of vitamin D as a result of its immune-regulatory mechanisms was not reached. Larger scale studies might pave the way to define vitamin D benefits in postmenopausal osteoporosis. [GMJ.2019;8:e1548]